Sistem Informasi Akuntansi Dan Pengendalian Internal Atas Pembelian Bahan Baku - Lasmini, Lilis; Nasihin, Ihsan; Nurdiansyah, Hendri (Gorontalo Accounting Journal, 2023)
The purpose of this study is to determine the implementation of purchasing accounting information systems and internal control over the purchase of raw materials. This study uses a qualitative method using an interpretive paradigm and a case study approach. The data used in this study are primary data, such as the company's organizational structure, operational system procedures, and enterprise resource planning systems that are implemented in the company. The results of the research that has been done show that PT Standard Indonesia Industri (SII) at the time of implementing the accounting information system and internal control of raw materials had good and neat documents related to purchases, making it easier to record. Plus PT Standard Indonesia Industri (SII) has procedures or standard operating procedures that are good enough so that they can maintain and control the stock of raw materials for the production process.